Target and Learning Need Analysis of Creative Writing Course: What Students Need? - Titis Yekti Lestari (Melekliterasi Press, 2024)
Writing skills are one of the skills that must be mastered by every student in higher education, especially in a Creative Writing course. This research aims to discover the targets and learning needs of the students when taking a Creative Writing course in movie script writing. To obtain the necessary data, this research used a questionnaire and interview. The type of research used is descriptive qualitative. The participants in this research were students in the fifth semester of the Creative Writing course. The findings in this research indicate that students need a clear understanding and guidance regarding the steps for writing a movie script in the Creative Writing course. It can be concluded that an analysis of the target and learning needs is needed as a pivotal point since it makes students better at writing movie scripts in the Creative Writing course.